Zooming in on a sleeping giant: milliarcsecond High Sensitivity Array imaging of the black hole binary V404 Cyg in quiescence - Miller-Jones, James; Gallo, E.; Rupen, M.; Mioduszewski, A.; Brisken, W.; Fender, R.; Jonker, P.; Maccarone, T. (Wiley-Blackwell Publishing Ltd., 2008)
Observations of the black hole X-ray binary V404 Cyg with the very long baseline interferometer the High Sensitivity Array (HSA) have detected the source at a frequency of 8.4 GHz, providing a source position accurate to 0.3 mas relative to the calibrator source. The observations put an upper limit of 1.3 mas on the source size (5.2 au at 4 kpc) and a lower limit of 7 × 10^6 K on its brightness temperature during the normal quiescent state, implying that the radio emission must be non-thermal, most probably synchrotron radiation, possibly from a jet. The radio light curves show a short flare, with a rise time of ~30 min, confirming that the source remains active in the quiescent state.